Rational emotive behavioural therapy for enhancing social-emotional well-being of adolescents in Nigeria (2020)
This study utilized Rational Emotive Behavioural Therapy (REBT) in enhancing social emotional well-being among in school adolescents with the moderating effect of gender. The study adopted a pretest-posttest control group quasi-experimental design with a 2x2 factorial matrix. Two public secondary schools were randomly selected among secondary schools in Oyo State, Nigeria. Twenty-eight (29) participants with low self- esteem and socio-emotional well-being were partially randomised into REBT (14) and control (15) groups. The Intervention lasted eight weeks. The participants were screened and recruited based on scores falling below average on self-esteem scale and socio- emotional well-being scale. Three hypotheses were generated and tested at 0.05 level of significance using Analysis of covariance (ANCOVA) and Bonferonni Pairwise Comparison. There was a significant main effect of treatment on the socio-emotional well-being of the adolescents with low self-esteem (F (1, 24) = 49.971, p< 0.01, partial η2 = 0. 676). The participants in the REBT group had higher socio-emotional well-being (ẋ=44.27) than those in the control (ẋ=26.04) group. Among the participants in the REBT group, the male participants had higher (ẋ=39.42) score on socio-emotional well-being than their female counterparts (ẋ=30.89). There was no significant two-way interaction effect of treatment and gender on socio-emotional well-being of adolescents with low self-esteem (F (1, 24) = 0.009, p>0.05, η2=0.00). This implies that gender did not significantly moderate the effect of treatment on socio-emotional well-being of adolescents with low self-esteem. Rational Emotive Behavioural Therapy (REBT) was effective in the improvement of socio-emotional well-being of adolescents with low self-esteem. Psychotherapist in various educational settings should conduct continuous diagnosis among adolescents with unusual emotional display or withdrawal disposition. Teachers and parents should always refer adolescents going through emotional trauma or issues to the counsellor in Charge.